Single-Cell Sequencing Analysis of the db/db Mouse Hippocampus Reveals Cell-Type-Specific Insights Into the Pathobiology of Diabetes-Associated Cognitive Dysfunction - Ma, Shizhan; Bi, Wenkai; Liu, Xueying; Li, Shangbin; Qiu, Yaxin; Huang, Chengcheng; Lv, Renjun; Yin, Qingqing (Frontiers in Endocrinology, 2022)
Diabetes-associated cognitive decline (DCD), is one of the major complications of diabetes, characterized by a series of neurophysiological and pathological abnormalities caused by hyperglycemia. However, the precise pathogenesis of DCD is still poorly understood. Single-cell RNA sequencing (scRNA-seq) can discover rare subpopulations, explore functional heterogeneity and identify signaling pathways and potential markers. The aim of this study was to provide deeper insight into the complex network of molecular and cellular changes that underlie DCD, identify different cellular compartments of the diabetic mouse hippocampus at single-cell level, and elucidate the factors mediating the pathogenesis of DCD. To elucidate the hippocampal cell–specific gene expression changes in diabetic encephalopathy. Single-cell RNA sequencing was performed on hippocampus from db/m and db/db mice. Using subclustering analysis, we further characterised microglial cell subpopulations. Prominent findings were confirmed at the protein level using immunohistochemistry. This resulted in transcriptome data for 14621 hippocampus cells, which could be annotated to eleven distinct cell types. Analysis of differentially expressed genes in the microglia compartments indicated that infection- and inflammation- associated terms, immune system process and oxidative stress play important roles in the progression of DCD. Experiments at the protein level supported the activation of microglia, increased expression of inflammatory factors, oxidative stress damage in the hippocampus of db/db mice compared with db/m mice. In addition, a major finding in our study was that a subset of microglia that express genes related to pro-inflammatory disease-associated microglia (DAM). Our study identifies molecular pathways underlying inflammatory, and oxidative stress mediated changes in the db/db mouse model of DCD and may provide potential diagnostic biomarkers and therapeutic interventions against DCD.